The contribution of clinical mentoring to improving the quality of care for people living with HIV in a resource limited context in the provinces of Kinshasa and grand Bandundu, Democratic Republic of Congo (REVUE DES SCIENCES DE LA SANTE, 2026)
Improving the quality of care for people living with HIV remains a major challenge in resource-limited settings. Clinical tutoring has increasingly been implemented as a strategy to strengthen healthcare providers’ competencies; however, evidence documenting its operational contribution in the Democratic Republic of Congo remains limited. An analytical observational study using an uncontrolled before–after quasi-experimental design was conducted in health facilities located in Kinshasa and Grand Bandundu provinces. The analysis relied on aggregated programmatic data combined with qualitative information derived from clinical tutoring activities. The assessed indicators included HIV service performance measures and a composite quality-of-care score. An overall improvement in several programmatic and organizational indicators was observed during the study period, suggesting progressive strengthening of professional practices and service organization. The observed trends may be associated with clinical tutoring activities that promote adherence to clinical guidelines and workplace-based learning. However, the absence of a control group and the use of secondary programmatic data limit causal inference, requiring cautious interpretation of the findings. Clinical tutoring appears to be a promising strategy for supporting healthcare teams and progressively improving the quality of HIV services in resource-limited settings. Further studies using more robust methodological designs are needed to better determine its impact on health outcomes.
Keywords: Clinical tutoring; Quality of care; Management of PLHIV; HIV/AIDS; PMTCT; Democratic Republic of Congo